(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the knowledge of safe sexual behavior of students at Ninh Binh Medical College and to identify some factors related to this knowledge. Method: A cross-sectional study with analysis was conducted on 161 students selected by convenient sampling method. Data were collected through a questionnaire adapted from the Safe Sexual Behavior Questionnaire (SSBQ) scale, analyzed using SPSS 20 software with descriptive statistics and one-way ANOVA test. Results: The average score of knowledge of safe sexual behavior of students was 62.52 ± 12.38 points (out of a total of 108 points), at a fairly average level. Knowledge of using protective measures was higher than that of sexual communication skills and avoiding contact with body fluids. Female students, third-year students, those who had sex and those who lived with their families had higher scores, in which the difference between the group who had and had not had sex was statistically significant (p < 0.05). Conclusion: Students’ knowledge of safe sex is not comprehensive. It is necessary to strengthen comprehensive sex and reproductive health education in the formal training program and through appropriate extracurricular activities